2020
DOI: 10.1371/journal.pone.0242626
|View full text |Cite|
|
Sign up to set email alerts
|

TGF-β-induced activation of conjunctival fibroblasts is modulated by FGF-2 and substratum stiffness

Abstract: Purpose This study aimed to investigate the effects of substratum stiffness on the sensitivity of human conjunctival fibroblasts to transforming growth factor (TGF)-β, and to explore the molecular mechanism of action. Methods Human conjunctival fibroblasts were cultured on collagen-coated plastic or silicone plates. The stiffness of the silicone plates was 0.2 or 64 kPa. Cells were treated by 2.5 ng/mL TGF-β2 with or without fibroblast growth factor (FGF)-2 (0–100 ng/mL) for 24 h or 48 h. The protein express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 39 publications
(45 reference statements)
3
12
0
Order By: Relevance
“…For evaluating drug induced effects, 5 ng/mL solutions of TGF-β2, 10 ng/ml solutions of FGF-2, or both was added to 2D or 3D cultured Hcon F cells at Days 1 through 6. The dosages of the TGF-β2 and FGF-2 used in the present study were based on data reported in a previous study 25 , 26 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For evaluating drug induced effects, 5 ng/mL solutions of TGF-β2, 10 ng/ml solutions of FGF-2, or both was added to 2D or 3D cultured Hcon F cells at Days 1 through 6. The dosages of the TGF-β2 and FGF-2 used in the present study were based on data reported in a previous study 25 , 26 .…”
Section: Methodsmentioning
confidence: 99%
“…In this area, Kay et al reported that FGF-2 stimulates TGF-β-mediated cell proliferation in rabbit subconjunctival fibroblasts 24 . On the contrary, Matsumura et al reported that FGF-2 induces the of the TGF-β-mediated trans-differentiation within human conjunctival fibroblast (HconF) cells 25 .…”
Section: Introductionmentioning
confidence: 96%
“…The concentration of RNA samples was ascertained using a DS-11 NanoPad spectrophotometer (DeNovix, Wilmington, DE, USA). Reverse transcription and quantitative PCR were performed as previously described (63). Relative expression of the target mRNAs was compared to the control samples using the comparative threshold cycle method; glyceraldehyde-3-phosphate dehydrogenase was used as an endogenous control.…”
Section: Real Time Rt-pcrmentioning
confidence: 99%
“…The drug has been proven to inhibit TNF-alpha secretion in addition to other cytokines that cause the cytokine storm seen in SARS-CoV-2 patients [ 33 ]. Pirfenidone has also shown to decrease inflammatory response through inhibition of NLR family pyrin domain-containing (NLRP) 3, preventing the creation of an inflammasome complex that exacerbates COVID-induced inflammation [ 36 ]. In addition to its anti-inflammatory effects, pirfenidone also inhibits TGF- β -induced fibronectin synthesis as well as collagen 1 fibril formation [ 37 , 38 ].…”
Section: The Potential Prevention Of Lung Fibrosismentioning
confidence: 99%